Asymptotic Behavior of Logarithmic Potential of Zero Kind - Zabolotskii, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
Under a fairly general condition on the behavior of a Borel measure,we obtain unimprovable asymptotic formulas for its logarithmic potential.